2013
DOI: 10.1161/hypertensionaha.111.00436
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Association Analysis of Common Variants Influencing Antihypertensive Response to Hydrochlorothiazide

Abstract: To identify novel genes influencing blood pressure response to thiazide diuretic therapy for hypertension, we conducted genome-wide association meta-analyses of ≈1.1 million single nucleotide polymorphisms in a combined sample of 424 European Americans with primary hypertension treated with hydrochlorothiazide from the Pharmacogenomic Evaluation of Antihypertensive Responses Study (N=228) and the Genetic Epidemiology of Responses to Antihypertensive Study (N=196). Polymorphisms associated with blood pressure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 23 publications
1
117
0
Order By: Relevance
“…A recent genome-wide association study (44) found that polymorphic changes in only a very limited number of genes were associated with increases in blood pressure. The strongest linkage involved polymorphisms in the gene for PKC␣.…”
Section: Discussionmentioning
confidence: 99%
“…A recent genome-wide association study (44) found that polymorphic changes in only a very limited number of genes were associated with increases in blood pressure. The strongest linkage involved polymorphisms in the gene for PKC␣.…”
Section: Discussionmentioning
confidence: 99%
“…A combined association study of the PEAR, GERAS, and NORDIL trials highlighted a significant variant of PRKCA, protein kinase C alpha, as significantly associated with DBP reduction in response to thiazides 91 . The SNP, rs16960228, was replicated in the GENRES study cohort.…”
Section: Plausible Variants Uncovered In Unbiased Analysesmentioning
confidence: 99%
“…Significant individual differences in the therapeutic response to thiazides are observed, however (9). Moreover, genetic loss of NCC function in humans (6,10) and mice (3,11,12) causes a relatively mild salt-wasting phenotype, especially considering the significant contribution the thiazide-sensitive NCC makes to overall renal NaCl absorption.…”
Section: Introductionmentioning
confidence: 99%